Genome-wide characterization of lncRNAs and mRNAs in muscles with differential intramuscular fat contents - Sun, Yuanlu; Lin, Xu; Zhang, Qian; Pang, Yu; Zhang, Xiaohan; Zhao, Xuelian; Liu, Di; Yang, Xiuqin (Frontiers in Veterinary Science, 2022)
Meat quality is one of the most important traits in pig production. Long non-coding RNAs (lncRNAs) has been involved in diverse biological processes such as muscle development through regulating gene expression. However, studies on lncRNAs lag behind and a comparatively small number of lncRNAs have been identified in pigs. Also, effects of lncRNAs on meat quality remains to be characterized. Here, we analyzed lncRNAs in longissimus thoracis (LT) and semitendinosus (ST) muscles, being different in meat quality, with RNA-sequencing technology. A total of 500 differentially expressed lncRNAs (DELs) and 2094 protein-coding genes (DEGs) were identified. Through KEGG analysis on DELs we first made clear that fat deposition might be the main reason resulting in differential phenotype of LT and ST, for which cGMP-PKG and VEGF signaling pathways were the most important ones. Forty-one key DELs and 50 DEGs involved in differential fat deposition were then characterized. One of the key genes, cAMP-response element binding protein 1, was selected to confirm its role in porcine adipogenesis with molecular biology methods and found that it promotes the differentiation of porcine preadipocytes, consistent with its higher expression level and intramuscular fat contents in LT than that in ST muscle. Further-more, through integrated analysis of DELs and DEGs, transcription factors important for differential fat deposition were characterized among which BCL6 have the most target DEGs while MEF2A was targeted by the most DELs. The results provide candidate genes crucial for meat quality, which will contribute to improving meat quality with molecular breeding strategies.